Yeast concentration in the diet defines Drosophila metabolism of both parental and offspring generations - O. M. Strilbytska; N. P. Stefanyshyn; U. V. Semaniuk; O. V. Lushchak (The Ukrainian Biochemical Journal, 2021)
Parental dietary nutrients epigenetically influence offspring metabolism. Our analysis revealed unforeseen patterns in how enzymes of the main metabolic pathways respond to protein content in the diet. We reared parental flies Drosophila melanogaster on four types of diet with different dry yeast concentrations ranging from 0.25% to 15%. The subsequent generation was fed by the same diet, so the only variable in the experiments was the yeast concentration in the parental diet. We showed that protein restriction in the parental diet led to higher lactate dehydrogenase (LDH) activity in parents, and this effect was inherited in their progeny. The transgenerational effect of parental dietary yeast on malate dehydrogenase (MDH) activity was found only in males. An elevated level of dietary yeast was sufficient to enhance alanine transaminase ( ALT) and aspartate transaminase (AST) activity in parents, however, did not affect ALT activity and decreased AST in their offspring. A low yeast parental diet was shown to cause higher urea content in F1 males. It is concluded that parental dietary yeast plays a critical role in metabolic health that can be inherited through generation.Parental dietary nutrients epigenetically influence offspring metabolism. Our analysis revealed unforeseen patterns in how enzymes of the main metabolic pathways respond to protein content in the diet. We reared parental flies Drosophila melanogaster on four types of diet with different dry yeast concentrations ranging from 0.25% to 15%. The subsequent generation was fed by the same diet, so the only variable in the experiments was the yeast concentration in the parental diet. We showed that protein restriction in the parental diet led to higher lactate dehydrogenase (LDH) activity in parents, and this effect was inherited in their progeny. The transgenerational effect of parental dietary yeast on malate dehydrogenase (MDH) activity was found only in males. An elevated level of dietary yeast was sufficient to enhance alanine transaminase ( ALT) and aspartate transaminase (AST) activity in parents, however, did not affect ALT activity and decreased AST in their offspring. A low yeast parental diet was shown to cause higher urea content in F1 males. It is concluded that parental dietary yeast plays a critical role in metabolic health that can be inherited through generation.